Regulation of gene amplification and expression in cells that constitutively express a temperature sensitive SV40 T-antigen. - Portela, A (1985)
Simian cells have been transformed with SV40 origin-defective recombinant plasmids containing the tsA209 T-antigen gene. These plasmids contain deletions of either 5 or 52 nucleotides that include the BglI site at the SV40 ori, are defective for replication in COS-1 cells but retain a functional SV40 early promoter. Two cell lines transformed with these plasmids, U4 and S7, and their respective clonal derivatives E5 and F11, contain the tsA209 T-antigen gene integrated into the cell DNA and express T-antigen as detected by immunoprecipitation and immunofluorescence. These cells behave as ts-COS cells, since they complement in a temperature dependent manner the replication of an SV40 derived recombinant plasmid. When transfected with recombinant plasmids containing the chloramphenicol acetyl transferase (CAT) gene cloned into SV40 replicons, ts-COS cells were able to regulate the induction of the CAT activity by temperature. The ratios of CAT activity observed at permissive versus restrictive temperature were in the range of 20-400. Thus, these ts-COS cells are useful systems for the regulated expression of cloned genes in simian cells.